Tinboektoe toe: Spatial explorations - Greyling, S.F. (Literator, 2013)
In order to develop and advance research in the creative disciplines in a university context, it is important to create a space in which the expectations in the formal research environment and the unique features of the creative disciplines are in balance. To this end it is necessary to investigate more closely the challenges and possibilities of practice-based research approaches, and to understand their internal functioning better. The experimental and unique nature of artists’ books and the variety of activities that form part of the creative process may bring about an increased awareness of the creative process, and in that way it may also create space conducive for reflection. In this article the development of an artist’s book, Tinboektoe toe, being discussed, from the perspective of the reflective practitioner. This book, consisting of postcards, invited readers to literally and figuratively become part of the space of the book, to participate in its writing and to make stories, in order to dismantle and undermine the traditional boundaries of the narrative world and the book. Although reader participation in the construct of meaning underpins all writing, it became a deliberate and centrifugal force in this project, influencing the research themes and possibilities. This specific and nuanced focus is probably only feasible if a creative project and research issues are allowed to develop jointly organically. The project can be regarded as a case where artistic practice is the subject, method, content and outcome of research. Practice-based research must offer room for a journey of exploration and discovery.